Dual‐Color Emission from Monolithic m‐Plane Core–Shell InGaN/GaN Quantum Wells. Issue 6 (30th March 2021) - Kapoor, Akanksha; Grenier, Vincent; Robin, Eric; Bougerol, Catherine; Jacopin, Gwénolé; Gayral, Bruno; Tchernycheva, Maria; Eymery, Joël; Durand, Christophe
Abstract : A dual‐color emission is achieved combining two monolithic sets of core–shell multiple quantum wells (MQWs) grown on GaN microwires. The shell heterostructure is composed of 3× blue MQWs and 7× green MQWs with photoluminescence emission covering 400–450 and 450–550 nm wavelength bands, respectively. Both emissions are coming from the two MQW sets grown on m ‐plane sidewall surface, as revealed by cathodoluminescence mapping. Advanced structural characterization combining transmission electron microscopy and energy‐dispersive X‐ray analysis is performed on longitudinal cross‐sectional slices of the wires. Considering asymmetrical QW interface, the In content is measured to be equal to 15.7 (±0.5)% and 23.5 (±2.0)% in the first and the second MQW set consistent with the blue and green emissions. Extended defects are formed originating from the second MQW set due to higher In content. A flexible light‐emitting diode (LED) is fabricated based on these dual core–shell MQWs, showing an electroluminescence dominated by green emission due to efficient hole injection in the In‐rich second MQW set. This work opens the way for multiple color emission from core–shell MQWs for phosphor‐free nanowire‐based LED applications. Abstract : A dual‐color emission is achieved from GaN microwires combining two monolithic core–shell multiple quantum well (MQW) sets. The shell is composed of 3× blue and 7× green m ‐plane MQWs with In content measured equal to 15.7% and 23.5% covering 400–450 and 450–550 nm wavelength band emission, respectively. A flexible light‐emitting device integrating dual‐color wires is demonstrated.